eNOS Glu298Asp Polymorphism and Endothelial Dysfunction in Patients with and without End-stage Renal Disease - Ilhan, Nevin; Ates, Kadir; Ilhan, Necip; Kaman, Dilara; Celiker, Huseyin (Galenos Publ House, 2016)
Background: Chronic kidney diseases are known to influence nitric oxide metabolites (NOx) and asymmetric dimethylarginine (ADMA), though the exact mechanism is still poorly understood. Aims: The purpose of the present study was to examine eNOS Glu298Asp gene polymorphism, plasma NOx and ADMA concentration in subjects with and without End-stage Renal Disease. Study Design: Case-control study. Methods: In this study, genotype distributions of Glu298Asp in exon 7 of the eNOS gene polymorphisms in 130 hemodialysis and 64 peritoneal dialysis patients were compared with 92 controls. NOx was measured by using the Griess reaction while arginine, ADMA and SDMA measurements were performed by HPLC. Genotyping for eNOS Glu298Asp polymorphism was detected with the polymerase chain reaction and/or polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. Results: When the genotype frequencies of TT and GT genes were compared between both groups, there was no detected statistically important difference, eventhough a TT genotype frequency was 27 (20.8%) versus 17 (26.6%), GT heterozygote genotype frequency was 52 (40%) versus 22 (34.4%), and GG homozygote genotype frequency was 51 (39.2%) versus 25 (39.1%), respectively (p>0.05). NOx, SDMA and ADMA concentrations were significantly elevated in subjects with hemodialysis patients as compared to their corresponding controls. Whereas nitrite was found to be significantly decreased in the patient with peritoneal dialysis. Conclusion: Not observed any connection between the Glu298Asp polymorphism in the eNOS gene and end-stage Renal Diseases in our study population under different dialysis treatments. However, higher ADMA and SDMA concentrations in subjects with ESRD support the existing hypothesis that NOx overproduction affects endothelial dysfunction. Thus, the reduction of ADMA and SDMA concentrations might play a protective role in ESRD patients.
Keywords: eNOS Glu298Asp; endothelial dysfunction; end-stage renal disease